Pengembangan Aplikasi Kalla Reality Melalui Implementasi Teknologi Imersif Sebagai Media Promosi Dan Informasi Pada Bisnis Properti Hunian - Syarief Dienan Yahya; Muhammad Syafaat; Fizar Syafa’at (Prosiding SISFOTEK, 2023)
This research aims to develop the "Kalla Reality" application that integrates immersive technology (Virtual Reality and Augmented Reality) as a promotional tool and source of information in the real estate industry. The implementation of immersive technology in this application allows users to explore properties virtually, visualize details, and interact with realestate agents, providing a more interactive and informative experience. This research involves methodological steps including literature review, user needs analysis, application prototype development, immersive technology integration, testing, and final evaluation. The "Kalla Reality" application is designed to meet the needs of increasingly discerning consumers in choosing residential properties by providing rich information and in-depth visual experiences. The results of this research are expected to provide insights into the positive contribution of immersive technology to the residential real estate business, including increasing consumer interest, sales process efficiency, and brand image enhancement. This application can also serve as an example of how immersive technology can transform marketing and information paradigms in the real estate industry and inspire further development in this field. Thus, this research reflects the role of immersive technology in enhancing consumer experiences, business efficiency, and the competitiveness of residential real estate companies in a competitive market.